2013
DOI: 10.1002/ceat.201200592
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Lavandin Essential Oil in Poly‐(ϵ‐caprolactones) by PGSS Process

Abstract: Lavandin essential oil has been encapsulated in poly‐(ϵ‐caprolactone) (MW: 4000 g mol–1) by means of the particles from gas saturated solutions (PGSS) process. The influence of process conditions, i.e., pre‐expansion temperature and pressure, and oil/polymer mass ratio, on the morphology of particles and the efficiency of encapsulation has been analyzed. Spherical particles with particle sizes of 100–700 μm were obtained, with increasing particle sizes and more agglomeration as the oil/polymer ratio was increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Similar percentage yields have been reported in other studies using different terpene actives. 30,38 In this study, encapsulation efficiency was signicantly (p < 0.05) lower in PEG 4000 (61%), when compared to PCL 10000 (77%) or the polymeric blends (63-77%). Computed results showed that encapsulation efficiencies recorded in this study were either higher or within range of those previously reported in literature.…”
Section: Loading and Encapsulation Characteristicsmentioning
confidence: 51%
See 2 more Smart Citations
“…Similar percentage yields have been reported in other studies using different terpene actives. 30,38 In this study, encapsulation efficiency was signicantly (p < 0.05) lower in PEG 4000 (61%), when compared to PCL 10000 (77%) or the polymeric blends (63-77%). Computed results showed that encapsulation efficiencies recorded in this study were either higher or within range of those previously reported in literature.…”
Section: Loading and Encapsulation Characteristicsmentioning
confidence: 51%
“…Essential oils have been encapsulated in liposomes and polymers using scCO 2 techniques such as rapid expansion of supercritical solution (RESS) and particles from gas-saturated solution (PGSS) respectively. [27][28][29][30] The RESS technique employs scCO 2 as a solvent and uses organic co-solvents such as ethanol that can denature the bioactive with unwanted residual effect on the drug formulation. Unlike RESS that uses scCO 2 as a solvent, the PGSS process exploits the ability of scCO 2 to liquefy and plasticize a range of polymers such as polyethylene glycol (PEG) and polycaprolactone (PCL) at relatively high pressures and low temperatures by lowering the point at which the polymers melt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solution will then be expanded via a nozzle into a spray chamber at atmospheric pressure. The CO 2 gas then leaves the gas-saturated polymer/fat droplets and also during expansion, the temperature of the mixture reduces drastically due to the Joule–Thomson effect, hence causing the polymer solidification [88]. A similar process termed as supercritical melt micronization (ScMM) has been developed for the micronization of fats (such as hard fats or milk fats) [89,90,91,92].…”
Section: Role Of Supercritical Carbon Dioxide In Microencapsulatiomentioning
confidence: 99%
“…After this first study, the literature is abundant on PGSS findings showing the potential of the technique for the micronization of food ingredients and bioactive compounds such as mackerel reaction oil [ 66 ], menthol [ 70 ], β-carotene [ 30 ] and several essential oils [ 39 , 59 , 71 , 75 ]. In most of the studies, polyethylene glycol has been used as carrier material for the encapsulation and protection of bioactives.…”
Section: Supercritical Carbon Dioxide Technologies For the Encapsumentioning
confidence: 99%